2015
DOI: 10.1089/scd.2014.0569
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Rybp in Mouse Embryonic Stem Cells Impairs Cardiac Differentiation

Abstract: Ring1 and Yy1 Binding Protein (Rybp) has been implicated in transcriptional regulation, apoptotic signaling and as a member of the polycomb repressive complex 1 has important function in regulating pluripotency and differentiation of embryonic stem cells. Earlier, we have proven that Rybp plays essential role in mouse embryonic and central nervous system development. This work identifies Rybp, as a critical regulator of heart development. Rybp is readily detectable in the developing mouse heart from day 8.5 of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(53 citation statements)
references
References 33 publications
2
48
0
3
Order By: Relevance
“…Parallel in vitro studies also showed that Rybp has important role in differentiation of stem cells. Whilst the Rybp −/− ES cells are viable, can proliferate and can be maintained for an unlimited time, they do not form contractile cardiomyocytes (CMCs) ( Table 2) [244], and form less matured neurons, astrocytes and oligodendrocytes in vitro (Table 2) [245]. These results are in agreement with previous in vivo studies suggesting the role of Rybp in differentiation rather than self-renewal [166,240].…”
Section: Core Members Of Ncprcssupporting
confidence: 88%
See 1 more Smart Citation
“…Parallel in vitro studies also showed that Rybp has important role in differentiation of stem cells. Whilst the Rybp −/− ES cells are viable, can proliferate and can be maintained for an unlimited time, they do not form contractile cardiomyocytes (CMCs) ( Table 2) [244], and form less matured neurons, astrocytes and oligodendrocytes in vitro (Table 2) [245]. These results are in agreement with previous in vivo studies suggesting the role of Rybp in differentiation rather than self-renewal [166,240].…”
Section: Core Members Of Ncprcssupporting
confidence: 88%
“…The majority of these mutations were generated decades ago [148], before the discovery of the canonical and non-canonical PRC1 complexes. Gene ablation of the non-canonical RYBP subunit results peri-implantational lethality in mice [166] and ES cells have compromised differentiation abilities [244,245]. Gene ablation of two ncPRC1.1 members, Usp7 [294] and Kdm2b [280], or the ncPRC1.6 member l3mbtl2, is also embryonic lethal [215], which highlights their essential function in embryogenesis.…”
Section: The Function Of Ncprc1 Subunits Are Often Essential For Mammmentioning
confidence: 99%
“…In our experimental system expression of mesodermal marker Gsc was increased 3x at d7 in both cell lines ( Figure 11A) and there was no difference in Gsc expression between the cell lines. This coincides with our previous observations when during in vitro cardiac differentiation both early mesodermal markers Gsc and Brachyury were expressed as expected but the rybp -/-cells were not able to produce contractible cardiomyocytes (Ujhelly et al, 2015). This result shows that the lack of Rybp influences differentiation at later stages rather then mesoderm formation.…”
Section: Major Germ Layer Formation Was Not Impaired In the Rybp Nullsupporting
confidence: 92%
“…By constructing four RYBP mouse models, this team also showed that dysregulated RYBP expression resulted in retinal coloboma, malformed lenses, defects in anterior eye development and corneal neovascularization, indicating that RYBP plays critical roles in mouse eye development [12]. Additionally, Ujhelly et al suggested that RYBP is also important for both cardiac and germ cell development [13]. In terms of cardiac development, the absence of RYBP in ESCs blocked cardiac differentiation to contractile cardiomyocytes, possibly through regulation of the expression of Plagl1, Isl1 and Tnnt2 genes.…”
Section: The Roles Of Rybp In Developmentmentioning
confidence: 98%
“…In terms of cardiac development, the absence of RYBP in ESCs blocked cardiac differentiation to contractile cardiomyocytes, possibly through regulation of the expression of Plagl1, Isl1 and Tnnt2 genes. Furthermore, these impaired phenotypes were rescued by ectopic expression of RYBP using a lentivirus vector [13]. In contrast to the active function in development, Zhou et al found that the expression of RYBP and its binding protein YY1 were gradually decreased during C2C12 myoblast differentiation, accompanied by miR-29 overexpression, indicating that RYBP acts as a repressor of skeletal myogenesis [14].…”
Section: The Roles Of Rybp In Developmentmentioning
confidence: 99%